Sociodemographic and Obesity-Related Disparities in Risks of Inadequate and Excessive Intake of Micronutrients During Pregnancy: The National ECHO Consortium. (7th June 2021) - Sauder, Katherine; Harte, Robyn; Ringham, Brandy; Guenther, Patricia; Bailey, Regan; Dunlop, Anne; Elliott, Amy; Hedderson, Monique; Avalos, Lyndsay; Zhu, Yeyi; Breton, Carrie; Chatzi, Lida; et al.
Abstract: Objectives: Both inadequate and excessive intake of micronutrients in pregnancy have the potential to negatively impact child health outcomes. We examined micronutrient intake in a large, diverse sample of women with singleton pregnancies across the United States, including intake by maternal age, race/ethnicity, education, and pre-pregnancy body mass index (BMI). Methods: Fifteen observational cohorts in the Environmental influences on Child Health Outcomes (ECHO) consortium assessed prenatal food intake and dietary supplement use with 24-hour dietary recalls (5 cohorts; 1859 women) or food frequency questionnaires (10 cohorts; 8064 women) from 1999–2019. We compared mean daily intake of 19 micronutrients to the age-specific estimated average requirement (EAR), adequate intake (AI), and tolerable upper intake level (UL) for pregnancy, overall and within sociodemographic and anthropometric subgroups. For recall data, we used a measurement error method to estimate distributions of usual intake, proportion below the EAR/AI, and above the UL. For FFQ data, we calculated the proportion below the EAR/AI and above the UL. Results: Risk of inadequate intake from foods alone ranged from 0–93%, depending on the micronutrient or assessment method. With dietary supplements, more than 1 in 5 women remained at risk for inadequate intake of choline, magnesium, and vitamins D, E, and K; or excessive intake of folic acid, iron, and zinc. Higher risks for inadequate intakes were observed among women with obesity (magnesium, vitamin K), who were <18 years (magnesium, vitamin K), Hispanic (vitamin E), non-Hispanic Black (vitamin K), non-Hispanic White (choline) or less educated (magnesium, vitamin E) when compared to counterparts. Conclusions: Improved diet quality is needed for most pregnant women. Even with a high prevalence of dietary supplement use, at least 1 in 5 pregnant women were at risk of inadequate intake of ≥ 1 micronutrients, especially in some population subgroups. Pregnancy may be a window of opportunity to address disparities in micronutrient intake that could contribute to intergenerational health inequalities. Funding Sources: National Institutes of Health, Environmental Protection Agency, Autism Speaks.